Dialog über die Liebe - Amatorius Plutarch - Plutarch, undefined (SAPERE, 2018)
Plutarch gives Plato's philosophy of love a new direction by applying its basic ideas to marital love and by defending the significance of sexuality for personality development and human bonding. This work is presented here with a literary-oriented introduction, the Greek text has been checked carefully, the German translation aims to be readable and is supplemented by detailed notes. Four essays by various authors are included.